A special BEM for elastostatic analysis of building floor slabs on columns - Neto, L. D.; de Paiva, J. B. (Elsevier B.V., 2003)
This work presents a boundary element formulation for the analysis of building floor slabs, without beams, in which columns are coupled with the plate. An alternative formulation of boundary element method is presented, which considers three nodal displacements values (w, partial derivativew/partial derivativen and partial derivativew/partial derivatives) for the nodes at the boundary of the plate. In this formulation three boundary equations are written for all nodes at the boundary and in the domain of the plate. As the nodes of the column-plate connections are also represented by three nodal values, all these structural elements can be easily coupled. It is supposed that the cross-sections of the columns remain flat after the deflection and consequently the assumption of linear variation of the stress in the plate-column contact surface is also valid. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: boundary element method; plate bending; interaction plate-columns; building slabs